Pregnancy-related Anxiety Scale (The PrAS): Validity and reliability study of its Turkish version - Şolt Kırca, Ayça; Kanza Gül, Derya (Celal Bayar Üniversitesi, 2020)
Objective: Women may have anxiety during pregnancy. This anxiety may have adverse results both for women and their infants. A scale is needed to determine this anxiety, that occurs during pregnancy, psychometrically. This study aims to conduct the reliability and validity study of the PrAS in Turkish population. Materials and Methods: The study was designed methodologically. The data of the study were collected in the Obstetrics Outpatient clinic of a private hospital located in Istanbul. The participants were composed of 495 pregnant women (primiparous and multiparous). Results: The internal consistency of the Turkish version of the PrAS (Cronbach's alpha = 0.85), the correlation coefficient of the items (0.27 and 0.57) and the confirmatory factor analysis (CFA= 0.35 and 0.98) were found to be high. The PrAS had a high correlation with PRAQ-R2 (multiparous pregnant women r= 0.60, primiparous pregnant women r= 0.65, p= 0.000) Conclusion: It was demonstrated that the Turkish version of the PrAS was a reliable and valid instrument to assess the anxiety level experienced during pregnancy and this instrument may be easily adapted to other languages.

Giriş ve Amaç: Kadınların hamilelik sırasında endişeleri olabilir. Bu kaygı hem kadınlar hem de bebekleri için olumsuz sonuçlara neden olabilir. Hamilelik sırasında ortaya çıkan bu kaygıyı psikometrik olarak belirlemek için bir ölçek gereklidir. Bu çalışma, Türk toplumunda PrAS'ın güvenilirlik ve geçerlilik çalışmasını yürütmeyi amaçlamaktadır. Gereç ve Yöntemler: Çalışma metodolojik olarak tasarlanmıştır. Çalışmanın verileri İstanbul'da bulunan özel bir hastanenin Kadın Hastalıkları Polikliniğinde toplandı. Katılımcılar 495 gebeden (primiparous ve multiparous) oluştu. Bulgular: PrAS'ın Türkçe versiyonunun iç tutarlılığı (Cronbach's alpha = 0.85), maddelerin korelasyon katsayısı (0.27 ve 0.57) ve doğrulayıcı faktör analizi (CFA = 0.35 ve 0.98) yüksek bulunmuştur. Pras'ın PRAQ-R2 ile yüksek korelasyonu vardı (çok sayıda gebe kadın r = 0.60, ilkel gebe kadın r = 0.65, p = 0.000) Sonuç: PrAS'ın Türkçe versiyonunun gebelik sırasında yaşanan kaygı düzeyini değerlendirmek için güvenilir ve geçerli bir araç olduğu gösterilmiştir ve bu araç diğer dillere kolayca uyarlanabilir.
Gebelik ile ilişkili anksiyete ölçeği: Türkçe geçerlilik ve güvenirlik çalışması
Keywords: Anxiety; Midwife; Nursing; Pregnancy; Reliability; Turkish Adaptation; Validity; Anksiyete; Ebe; Gebelik; Geçerlik; Güvenirlik; Hemşirelik; Türkçeye Uyum